Fintech, MSME Digitalization, Financial Literacy and Financial Performance: A Study on MSMEs in Bandar Lampung City - laurensia Laurensia; Luke Suciyati Amna; Aminah Aminah (Cita konsultindo, 2024)
The evolution of information technology has played an important role in the development of the business world. Business actors are expected to be able to take advantage of the various innovations provided by the technology. The purpose of this study was to examine the effect of fintech, digitalization, and financial literacy on the financial performance of MSMEs in Bandar Lampung City. This research was conducted by surveying MSME players in the culinary sector in Bandar Lampung City. This research uses quantitative descriptive methods. The technique used is convenience sampling by distributing Likert scale questionnaires, and this data is processed using SPSS version 23. The results showed that payment gateway-based fintech, digital marketing, and financial literacy moderated the effect of fintech payment gateways and digital marketing on the financial performance of MSMEs. The findings of this research provide benefits for MSME players in developing their businesses by paying attention to aspects of digital technology and financial literacy so that financial performance increases.